(untitled) (Journal of Patan Academy of Health Sciences, 2022)
Introduction: Patan Academy of Health Sciences (PAHS) decided to test mental agility and personal qualities to select undergraduate medical students, which was different than the conventional approach used in other health science universities in Nepal. PAHS emphasized testing cognitive and non-cognitive abilities than physic, chemistry and biology contents and this study shows how it was done for selecting medical students in Nepal. Method: Personal Qualities Assessment (PQA) test batteries used to select medical students in twelve different countries were pilot tested with 10+2 non-science, 10+2 science and 10+3 health science students. PQA tools were forward translated in Nepali and back translated in English by bilingual experts independently. Face and content validity of these tools in Nepali language were established through discussions and consensus with the PAHS Admission team and PQA team in Australia. Result: PQA tools assessing non-cognitive qualities in Nepali language were found to be internally consistent in the first pre-test with science and non-science students. PQA tool assessing mental agility in English language showed acceptable internal consistency in the second pre-test with science and health science students. Conclusion: Mental agility test in English language is found to be suitable cognitive test for selecting medical students. Non-cognitive tests in Nepali language are found to be reliable and valid to identify applicants with unusual personal traits thereby leading to deselection. These tests can be considered for selecting undergraduate medical students at institute/university level or national level common entrance test in Nepal and beyond.